The importance of the Brazilian Society of Neurological Investigation (SBIN) - Camargo, Carlos Henrique Ferreira; Bazan, Rodrigo; Lange, Marcos Christiano; Zétola, Viviane Flumignan; Teive, Hélio Afonso Ghizoni (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2022)
The Brazilian Society of Neurological Research (SBIN) was founded on December 19, 2000, by a group of neurologists headed by Professor Lineu César Werneck, MD, Ph.D., to promote scientific development and cultural diversity in neurology and neurosciences. The criteria for members' admission have always been strict, and the group reached 80% of physicians with a Ph.D. degree. However, the conditions to become a member were modified to attract more researchers, especially the younger ones, and neuroscientists from other areas of health and biology. The scientific events were the primary goal of SBIN. Eighteen editions were performed. The board and members of the SBIN recognized that the Brazilian Academy of Neurology, and the other societies that encouraged the neurosciences, were working to continue the exponential increase of scientific production in the neurosciences in Brazil, realizing that their purposes were fulfilled. The society was dissolved in December 2020.
Keywords: History of medicine; Medical societies; Neurology; Neurosciences; Scientific societies